(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Chronic Obstructive Pulmonary Disease (COPD) causes irreversible airflow limitation, progressively worsening over time, and significantly impairs patients’ quality of life. Understanding the combined risk factors and the level of disease control will contribute to supplementing scientific evidence for disease management and prevention. The objective of this study is to identify factors associated with exacerbations requiring hospitalization among COPD outpatients. Methods: A cross-sectional descriptive study was conducted on 187 outpatients (stages 1-4) diagnosed with COPD at Viet Tiep Friendship Hospital, Hai Phong city from January to March 2025. Results: Most of the study subjects were over 60 years old (89.8%) and predominantly male (74.3%). The proportion of patients with exacerbations requiring hospitalization was 43.9%. The study identified factors that significantly increased the risk of hospitalization due to exacerbations, including having a history of smoking (OR = 2.40); mMRC dyspnea grade 4 (OR = 5.00); and severe COPD classifications such as Group C (OR = 5.10) and Group D (OR = 17.9). Conversely, factors that helped reduce the risk of hospitalization included: female gender (OR = 0.40 compared to male), education level above high school (OR = 0.56 compared to below high school), and the habit of regular physical exercise (OR = 0.50 compared to no exercise behavior). Conclusion: Gender, educational level, smoking history, physical exercise habits, degree of dyspnea (mMRC), and COPD classification are factors directly associated with hospitalization due to exacerbations in COPD patients.